2014
DOI: 10.1166/jnn.2014.9474
|View full text |Cite
|
Sign up to set email alerts
|

Initial Surface Reaction of Di-Isopropylaminosilane on a Fully Hydroxyl-Terminated Si (001) Surface

Abstract: We studied the interaction of di-isopropylaminosilane (SiH3N(C3H7)2, DIPAS) molecules with a fully hydroxyl-terminated Si (001) surface for SiO2 thin-film growth by using density functional theory. The amino group consisting of DIPAS was chosen in order to obtain a high adsorption energy because its lone-pair electrons in the N atom would help in the adsorption of DIPAS. The absolute value of the adsorption energy (0.67 eV) of DIPAS was higher than its reaction energy barrier of 0.38 eV. Thus, DIPAS could reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…12,25 Recently, various alkylaminosilane-based molecules with appropriately reactive functional ligands have been evaluated and tested with the aim to identify most suitable precursors for SiO 2 thin lm growth both experimentally [26][27][28][29][30][31][32] and theoretically. [15][16][17][33][34][35] It was found that an increase in the degree of alkylamino substitution on Si atom would result in a reduced deposition rate and a use of tris(alkylamino)silane-based precursors may lead to a higher degree of impurity in the lms, especially in a low temperature range of the ALD window. 18,36 For example, the dissociative chemisorption of tris(dimethylamino)silane (TDMAS) occurs only up to the second step with dimethylaminosilylenyl fragment anchored on the surface, which would give rise to surface impurity.…”
Section: Introductionmentioning
confidence: 99%
“…12,25 Recently, various alkylaminosilane-based molecules with appropriately reactive functional ligands have been evaluated and tested with the aim to identify most suitable precursors for SiO 2 thin lm growth both experimentally [26][27][28][29][30][31][32] and theoretically. [15][16][17][33][34][35] It was found that an increase in the degree of alkylamino substitution on Si atom would result in a reduced deposition rate and a use of tris(alkylamino)silane-based precursors may lead to a higher degree of impurity in the lms, especially in a low temperature range of the ALD window. 18,36 For example, the dissociative chemisorption of tris(dimethylamino)silane (TDMAS) occurs only up to the second step with dimethylaminosilylenyl fragment anchored on the surface, which would give rise to surface impurity.…”
Section: Introductionmentioning
confidence: 99%
“…The surface functional groups and their chemistry and density strongly influence the growth behavior in the ALD process. In the SiO 2 PE-ALD process, the Si–OH bonding, generally called the hydroxyl group, contributes to the ligand exchange reaction with diisopropylamino silane (DIPAS) (Si precursor) 15 , 24 . The Si–OH bonding on the surface is changed to Si (from the surface) –O–Si (from the DIPAS) –H 3 during the precursor feeding step 24 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PBE-D2 predictions have proven useful for prediction of the dissociative reactions of various molecules on different surfaces as shown by the numerous studies on the dissociation of different large molecules on Au (gold), 46 oxygen reduction reaction on Co(acetylaetonate) 2 , 47 water dissociation on mackinawite (FeS), 48,49 and the dissociative reaction of silicon precursor on Si. 50 To calculate the transition state, the distance between the two dissociative atoms was slightly separated, and energy relaxation was performed with the constrained distance. The same procedures were carried out until the force between two dissociative atoms became almost zero at the saddle point energy.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, PBE-D2 predictions have proven useful for prediction of the dissociative reactions of various molecules on different surfaces as shown by the numerous studies on the dissociation of different large molecules on Au (gold), 46 oxygen reduction reaction on Co(acetylaetonate) 2 , 47 water dissociation on mackinawite (FeS), 48,49 and the dissociative reaction of silicon precursor on Si. 50 …”
Section: Methodsmentioning
confidence: 99%